Precision orchard sprayer based on automatically infrared target detecting and electrostatic spraying techniques - Xiongkui, He; Aijun, Zeng; Yajia, Liu; Jianli, Song (International Journal of Agricultural and Biological Engineering, 2011)
Abstract: There is an urgent need for new chemical application techniques and sprayers in Chinese orchard spraying. A new tractor-mounted automatic target detecting electrostatics, and air-assisted orchard sprayer was designed and developed to meet the demand of chemical pest control in orchards. This sprayer light weighted, highly efficient, reduces pesticide use and is friendly to the environment. The techniques of automatic target detecting, electrostatics, and air-assisted spraying were combined in this system. The electrostatically charged droplets are projected toward the target by the assistance of an air stream that increases the droplets penetration within canopy. Experimental results show that the new automatic target detecting orchard sprayer with an infrared sensor can save more than 50% to 75% of pesticides, improve the utilization rate (over 55%), control efficiency, and significantly reduce environmental pollution caused by the pesticide application. At the same time the key technological problems related to air-assisted low volume and electrostatic spraying were solved. Keywords: precision spraying, orchard sprayer, automatic target plant detection, air assisted spray, electrostatic spray DOI: 10.3965/j.issn.1934-6344.2011.01.035-040 Citation: He Xiongkui, Zeng Aijun, Liu Yajia, Song Jianli. Precision orchard sprayer based on automatically infrared target detecting and electrostatic spraying techniques. Int J Agric & Biol Eng, 2011; 4(1): 35<span style="font-size: 9pt; line-height: 140%; font-family: